Piloting a classification framework for the types of evidence used in alcohol policymaking - Kowalski, M.; Wilkinson, C.; Livingston, Michael; Ritter, A. (WILEY, 2023)
Introduction: Most studies of alcohol policy have focussed on the role of industry. However, little is known about the evidence base used in alcohol policymaking or policymakers' actions in the field. Here, we mapped the different evidence types used in a case study to construct a classification framework of the evidence types used in alcohol policymaking. Methods: Using a case study from the state-level in Australia, we used content analysis to delineate the evidence types cited across six phases of a policymaking process. We then grouped these types into a higher-level classification framework. We used descriptive statistics to study how the different evidence types were used in the policymaking process. Results: Thirty-one evidence types were identified in the case study, across four classes of knowledge: person knowledge, shared knowledge, studied knowledge and practice knowledge. The participating public preferenced studied knowledge. Policymakers preferenced practice knowledge over all other types of knowledge. Discussion and Conclusion: The classification framework expands on models of evidence and knowledge used across public health, by mapping new evidence types and proposing an inductive method of classification. The policymakers' preferences found here are in line with theories regarding the alcohol industry's influence on policymaking. The classification framework piloted here can provide a useful tool to examine the evidence base used in decision-making. Further study of evidence types used in policymaking processes can help inform research translation and advocacy efforts to produce healthier alcohol policies.